Meningkatkan Rasa Percaya Diri pada Anak Melalui Kegiatan Bernyanyi Asik di RA Nurul Wahid Al-Wahyuni - Nur Indah Kumala Sari; Ivonne hafidlatil kiromi (Zuriah Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to explore the influence of the "joyful singing" activity on enhancing selfconfidence among young children at RA Nurul Wahid Al-wahyuni. An observational method was employed to observe children's interactions during the "joyful singing" sessions and identify its impact on the development of self-confidence. The observation results revealed an increase in social interactions and emotional expressions among children during the singing activity. This suggests that the "joyful singing" activity provides a supportive environment for children to feel comfortable expressing themselves and engaging with their peers. The study provides insights into the significance of enjoyable and creative approaches in early childhood education to assist children in building their self-confidence. Therefore, it is recommended for early childhood educational institutions to consider integrating the "joyful singing" activity into the curriculum and creating an environment conducive to the holistic development of children.